Paid parental leave to immigrants: An obstacle to labor market entrance? - Ulrika Vikman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
This paper evaluates how access to paid parental leave affects labor market entrance for immigrating mothers with small children. Paid parental leave together with job protection may increase labor force participation among women but if it is too generous it may create incentives to stay out of the labor force. This incentive effect may be especially true for mothers immigrating to a country where having small children automatically makes the mothers eligible for the benefit. To evaluate the differences in the assimilation process for those who have access to the parental leave benefit and those who do not, Swedish administration data is used in a difference-in-differences specification to control for both time in the country and the age of the youngest child. The results show that labor market entrance is delayed for mothers and that they are less likely to be a part of the labor force for up to seven years after theír residence permit if they had access to parental leave benefits when they came to Sweden. This reduction in the labor force participation is to some extent driven by unemployment since the effect on employment is smaller. But there is still an effect on employment of 3 percentage points lower participation rates 2-6 years after immigration.
Keywords: J13; J15; J21; 330; immigrant assimilation; labor market entrance; paid parental leave benefit; Arbeitsangebot; Elternzeit; Mütter; Migranten; Soziale Integration; Schweden